The Correlation Study Between Students’ Metacognitive Strategy and Self-Efficacy in Learning English - Afdal, Taufik; Mayasari, Eka; Anwar, Nurul (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
The objective of this research was to find out the correlation between students’ metacognitive strategy and their self-efficacy in speaking skills at the third grade of language major of MAN Tanjungpinang. The subject of this research was all of the students of the third grade of language major of MAN Tanjungpinang. The object of the research is students in the third grade of language major of MAN Tanjungpinang. The population of this research was 197 students of the third grade in MAN Tanjungpinang with 19 of the students being used as samples of the research. To collect the data, the researcher used observation and questionnaires. To analyze the data the researcher used descriptive statistics with a Pearson Product Moment and tested of the significance of the correlation coefficient. The result indicated that the value of the correlation coefficient (r) is 0.425, with level of correlation is moderate because it is in the coefficient interval between 0.40 - 0.599, while the value of tcomputed is greater than the value ttable (1,935>1,734) and the significance value is 0,035, which is 0,035<0,05 (1-tailed). H0 is rejected and Ha is accepted. It means that there is a significant correlation between students’ metacognitive strategy and their self-efficacy in speaking at the third grade of language major of MAN Tanjungpinang at 0,05 level (1-tailed).